Sputtering pressure influence on growth morphology, surface roughness, and electrical resistivity for strong anisotropy beryllium film - 罗炳池 李恺 康晓丽 张吉强 何玉丹 罗江山 吴卫东 唐永建 (Chinese physics B, 2014)
The strong anisotropy beryllium （Be） films are fabricated at different sputtering pressures by direct current magnetron sputtering. With the increase of pressure, the deposition rate of Be film first increases, and when the pressure exceeds 0.8 Pa, it gradually descends. The X-ray diffraction analysis indicates that Be film is of α-Be phase, its surface always reveals the （101） crystal plane possessing the low surface energy. As for the growth morphology of Be film, the surface is mainly characterized by the fibrous grains, while the cross section shows a transition from a columnar grain to a mixed grain consisting of a cone-shaped grain and a columnar grain as the sputtering pressure increases. The large grain fraction decays exponentially from 75.0% to 59.3% with the increase of sputtering pressure p, which can improve the grain size uniformity. The surface roughness increases due to the insufficient atom diffusion, which is comparable to its decrease due to the etching effect at p 〈 0.8 Pa, while it increases drastically at p 〉 0.8 Pa, and this increase is dominated by the atom diffusion. The electrical resistivity values of Be films range from 1.7 μΩ m to 2.7 μΩ m in the range 0.4 Pa-1.2 Pa, which is 50 times larger than the bulk resistivity.